Factors Affecting Intention To Visit Riau Islands - Keni Keni; Rafaela Winata (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study aims to empirically test 1) destination quality, destination image, and natural and cultural attractions on intention to visit. 2) destination quality and destination image on tourist satisfaction. 3) tourist satisfaction on intention to visit. 4) destination quality and destination image on intention to visit through tourist satisfaction. Data was collected using an online questionnaire from 221 respondents who are tourists which have visited Riau Islands in the last three years, then examined using PLS-SEM. The results indicate that only destination quality could not predict intention to visit directly, while all other variables are able to predict intention to visit positively and significantly. This research is expected to be a reference for Dinas Pariwisata of Riau Islands Province in determining an effective strategy by knowing tourists’ most needed and preferred factors in order to increase the intention to visit, as well as the tourism competitive advantage of Riau Islands.